Comparison of compressive stress in temporary crowns fabricated by two 3D printers: Asiga and Quick Digi - Motaghian , Alireza; Razeghi, Mehdi; Shafigh , Mohammad (Social Determinants of Health, 2026)
Background: The mechanical strength and longevity of 3D-printed dental temporary crowns are significantly influenced by layer thickness and printer type. The purpose of this study was to assess how layer thickness and printer type affected the temporary crowns' mechanical robustness. Methods: In this in vitro study, 60 temporary crown samples were fabricated using two 3D printers, Asiga and Quick Digi. Thirty samples per thickness were printed at two-layer thicknesses of 50 μm and 60 μm. Descriptive statistics, paired t-tests, one-sample t-tests, and correlation analysis were used to examine the data after compressive strength was determined. Results: The mean compressive strength was 230.33 kg/m² for 50 μm and 124.50 kg/m² for 60 μm. The two thicknesses differed significantly (p < 0.001), according to the paired t-test. The mean percentage change in compressive strength was -45.67%, showing a uniform and consistent reduction across all samples. Correlation analysis revealed no significant linear relationship between mechanical performance at the two thicknesses. Comparative analysis between the two printers indicated superior performance of Asiga in strength and structural uniformity. Conclusion: Selecting an appropriate layer thickness and high-quality 3D printer is crucial for enhancing the mechanical strength and durability of temporary crowns and can guide clinical decision-making in digital dentistry.